LANGUAGE DIGLOSIA IN BUGIS COMMUNITY INTERACTION - Fahriadi Muhdar; Alfiani Alfiani; Taslim Taslim (Journal Analytica Islamica, 2025)
In Indonesia, various languages can be learned by all levels of society, both teenagers and adults. Language variety is a variety of language that is used differently, namely it is divided into two, namely high language variety and low language variety. Research on the use of these two varieties of language will emphasize language diglossia in the interactions of the Bugis community in everyday life. The aim of this research is to find out what and how the Bugis community interacts in language diglossia or the two varieties used in everyday life. The method used in this research is observation by observing what and how the Bugis community interacts in two different languages in diglossia. The results of this research will identify speech or interactions that refer to diglossia and compare the two varieties of language used in Bugis community interactions.